PEMBERDAYAAN SUBAK DALAM APLIKASI TEKNOLOGI PEMUPUKAN SPESIFIK LOKASI DI DESA MEGATI KECAMATAN SELEMADEG TIMUR KABUPATEN TABANAN - I.N. Sunarta; I.N. Dibia; N.M. Trigunasih; I.D.M. Arthagama; T. Kusmawati (Buletin Udayana Mengabdi, 2017)
Increased development in all fields must be supported with food security is primarily rice. Production of rice in Bali is synonymous with productivity wetland managed by Subak. The purpose of this service is to introduce a site-specific nutrient fertilization program; transformation of knowledge in the management of wetland (Subak); Increased harmonious relationship among members and administrators Subak; Increasing farmers' understanding and skills in the application of site-specific nutrient fertilizer (SSNF) for rice research in Subak Blong Yang Kelod Megati Kaja village. Desirable specific targets in this devotion is to increase the ability and skills of farmers Subak members Blong Yang Kelod in implementing site-specific nutrient fertilization either time, types and doses of fertilizers applied to rice crops in accordance IRRI program. It is expected to impact on improving the livelihoods of farmers and the growing understanding and commitment to care for the preservation of Subak. Implementation of community service activities begins with Dissemination of paddy fertilizer technology specific location based IRRI program with http://webapps.irri.org/nm/id. devices. Implementation of dissemination held on October 28, 2016 in Subak Blong Yang Kelod, Megati village. Subak members are very enthusiastic about the explanation given SSNF through several questions, including requests for training members of Subak, about organic fertilizer production with raw materials from cow manure and others. Based on the result of recommendations by the IRRI fertilizer 200kg / ha of NPK Kujang given at 0- 10 days after planting (DAP) and 100kg / ha of urea at the age of 23-27 DAP, 100kg / ha of urea in the 40-44 age DAP, then the rice production be increased from 6 t / ha into 6.4 t / ha of grain moisture content of 14%.